A Biologia acessível para surdos: propondo um modelo de material didático para o ensino de biomas - Magalhães, Paloma Jamily Cristina (Universidade Federal de São Carlos, 2017)
Throughout history the deaf have fought and still fight for their rights that are guaranteed by law, but despite all legislation, an idea has been created that to include the deaf student just insert it in the classroom of regular education. It is known that in order for inclusion to take place, effective action is needed by the school community and, especially, by teachers. The use of methodological strategies is relevant in the teaching of the deaf because of their need for visuality, since it allows the deaf to create images and mental maps. This research justifies relevant and necessary access to the linguistic goods and knowledge to all deaf subjects using Libras, in compliance with the Accessibility Law n. 10.436 / 02 and Decree n. 5.625 / 05, as well as for bringing an alternative to the teaching of biomes accessible to the deaf, aiming to broaden pedagogical practices for the effective inclusion of deaf students in the regular classroom. With this in mind, this work seeks to investigate the teaching of biology in an accessible way for deaf students, from the analysis of articles that address the teaching of biology for the deaf, focusing on their methodologies. To reflect on the importance of the methodological strategies for deaf students and, finally, to propose a model of didactic material for teaching Biomas in an accessible way for deaf students. For this, a bibliographical review was carried out based on searches in research sites, specific sites and also in a specific magazine of didactic materials. The research evidenced that there are more works on methodological strategies and didactic materials in the teaching of Sciences / Biology for deaf students in research sites than in specific sources of special education and didactic material. Thus, it is imperative to think about education and to reflect on pedagogical practices, especially on the use of strategies for the teaching of the deaf so that they can have access to scientific knowledge, since it is the teacher's duty to seek ways of include the deaf student in the classroom and activities as well as actions that promote teamwork, inclusion and autonomy of the deaf.
Accessible Biology for the deaf: proposing a teaching material model for teaching biomes
Keywords: Educação de surdos; Ensino de Ciências; Estratégias metodológicas; Deaf education; Science teaching; Methodological strategies; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS BIOLOGICAS; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL